2006
DOI: 10.1002/lt.20811
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial- and fungal-positive cultures in organ donors: Clinical impact in liver transplantation

Abstract: Infection transmission from donor to recipient is a dreadful complication in transplantation. Although bacteremia was previously detected in 5% of donors without negative impact on recipient outcome, the current expansion of graft pool requires consideration of the infectious risk associated with suboptimal donors. This study aims to evaluate the incidence and risk factors of infection in unselected cadaveric liver donors, the occurrence of microorganism transmission to recipient and its influence on patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
110
3
8

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 23 publications
8
110
3
8
Order By: Relevance
“…and several others. 4,5,17 All of the aforementioned agents were found in this study, totaling 71% of all microorganisms.…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…and several others. 4,5,17 All of the aforementioned agents were found in this study, totaling 71% of all microorganisms.…”
Section: Methodsmentioning
confidence: 68%
“…In a study conducted by Cerutti et al, 5 mortality in the first year after transplant was significantly higher (5/11, 45%) when transmission of infection from donor to recipient occurred than when it did not (49/547, 9%). In a study, Len et al 20 demonstrated that the transmission of infection from donor to recipient was documented in 5 of 292 patients (1.71%), 2 of whom did not survive the infection (40%).…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…12,13 The rate of infection due to a donor organ infection is as low as 0.96% 8 with adequate preoperative antibiotic prophylaxis and aseptic organ retrieval. [14][15][16][17] We believe that adequately treated pretransplant cryptococcosis in a donor will not pose a significant risk of transmission.…”
mentioning
confidence: 98%